The level of competence of graduating nursing students in 10 European countries-Comparison between countries - Satu Kajander‐Unkuri; Sanna Koskinen; Anna Brugnolli; MªAngeles Cerezuela Torre; Imane Elonen; Viktorija Kiele; Daniela Lehwaldt; Eliisa Löyttyniemi; Jana Nemcová; Célia Simão deOliveira; Alvisa Palese; Marília Rua; et al. (Wiley, 2021)
Abstract Aim To analyse graduating nursing students' self‐assessed competence level in Europe at graduation, at the beginning of nursing career. Design An international cross‐sectional evaluative design. Methods Data were collected in February 2018-July 2019 from graduating nursing students in 10 European countries. Competence was assessed with a validated instrument, the Nurse Competence Scale (NCS). The sample comprised 3,490 students (response rate 45%), and data were analysed statistically. Results In all countries, graduating nursing students assessed their competence as good (range 50.0-69.1; VAS 0-100), albeit with statistically significant differences between countries. The assessments were highest in Iceland and lowest in Lithuania. Older students, those with working experience in health care, satisfied with their current degree programme, with excellent or good study achievements, graduating to 1st study choice and having a nursing career plan for future assessed their competence higher.